Sustancia, razón, libertad y pasión en Descartes: lecturas desde la modernidad temprana a la postmodernidad. - LÁZARO-CANTERO, RAQUEL; BEGON, JOAN LLUÍS LLINÀS; SANFÉLIX, VICENTE (Anuario Filosófico, 2024)
The following texts include the works of both senior scholars in cartesianism and novel researchers. Furthermore, they are part of a research project financed by the Ministerio de Ciencia e Innovación, [Referencia PID2021-126133NB-I00], titled Ethics and metaphysics of affections. The modern genesis of the present (EMAP). We are, therefore, offering the studies that resulted from this investigation, which began in September 2022.